High‐performance and flexible thermoelectric generator based on a robust carbon nanotube/BiSbTe foam - Myeong Hoon Jeong; Eun Jin Bae; Byoungwook Park; Jong‐Woon Ha; Mijeong Han; Young Hun Kang (Carbon Energy)
Abstract Organic thermoelectric generators (TEGs) are flexible and lightweight, but they often have high electrical resistance, poor output power, and low mechanical durability, because of which their thermoelectric performance is poor. We used a facile and rapid solvent evaporation process to prepare a robust carbon nanotube/Bi0.45Sb1.55Te3 (CNT/BST) foam with a high thermoelectric figure of merit (zT). The BST sub‐micronparticles effectively create an electrically conductive network within the three‐dimensional porous CNT foam to greatly improve the electrical conductivity and the Seebeck coefficient and reinforce the mechanical strength of the composite against applied stresses. The CNT/BST foam had a zT value of 7.8 × 10−3 at 300 K, which was 5.7 times higher than that of pristine CNT foam. We used the CNT/BST foam to fabricate a flexible TEG with an internal resistance of 12.3 Ω and an output power of 15.7 µW at a temperature difference of 21.8 K. The flexible TEG showed excellent stability and durability even after 10,000 bending cycles. Finally, we demonstrate the shapeability of the CNT/BST foam by fabricating a concave TEG with conformal contact on the surface of a cylindrical glass tube, which suggests its practical applicability as a thermal sensor.